Hubungan Curah Hujan terhadap Produktivitas Usaha Tani Cabai Rawit (Capsicum Frutescens L.) di Kecamatan Abiansemal, Kabupaten Badung - Pratiwi, Ni Kadek Indah; Dewi, Ni Luh Prima Kemala (IAI Nasional Laa Roiba Bogor, 2025)
Cayenne pepper (Capsicum frutescens L.) is a high value horticultural crop that plays an important role in Indonesia’s food sector. Its cultivation is highly affected by climatic factors, especially rainfall. In 2021, crop failure occurred in Abiansemal Subdistrict due to adverse weather. This study analyzes the relationship between rainfall and cayenne pepper productivity in the area. A quantitative method was used to assess rainfall impact, while qualitative data explored farming challenges. Primary data were collected through interviews with farmers and extension officers. Secondary data on production and harvested area were obtained from the Department of Agriculture and Food of Badung Regency, and rainfall data from BMKG’s Automatic Rainfall Gauge (ARG) in Abiansemal. Spearman correlation analysis using SPSS showed a strong negative correlation between rainfall and productivity (r = -0.900). Excessive rainfall likely led to waterlogging, root damage, and increased disease risk, contributing to yield decline. These results underscore the importance of climate aware farming practices and provide a useful reference for improving the resilience of cayenne pepper production.